ANALISIS HUBUNGAN IMPLEMENTASI DISIPLIN DALAM UPAYA PENINGKATAN KINERJA GURU PADA STUDI KASUS PADA SMA NEGERI 01 KOTO KAMPAR HULU - Aqsa, Muhammad Ali (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
Abstract, This study aims to analyze the implementation of the relationship betweendiscipline and teacher performance in SMA Negeri 01 Koto Kampar Hulu. By using a totalsample of 32 people. In this research, the writer used quantitative research method usingSPSS data processing system. From the results obtained, the r count variable of workdiscipline is 0.641 and the value of r table is 0.338. so that r count> r table (0.641> 0.338)and a significant value of 0.000 <0.05, so it means that there is a positive and significantrelationship between the discipline variable and the performance variable. Finally, from thisstudy it can be concluded that there is a positive and significant relationship betweendiscipline and teacher performance at SMA Negeri 01 Koto Kampar Hulu.